EKOKRITISISME DALAM NOVEL PANGGIL AKU SAKAI KARYA EDIRUSLAN PE AMANRIZA - Usman, Adek Feisal; Sinaga, Mangatur; Septyanti, Elvrin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research is entitled Ecocriticism in the Novel Panggil Aku Sakaiby Ediruslan PE Amanriza. This research is literary research regarding Ecocriticism inthe Novel Call Aku Sakai by Ediruslan PE Amanriza. The problem in this research isecocriticism which focuses on local environmental wisdom which is divided into fiveattitudes of observance 1) Attitudes of Respect towards Nature, 2) Attitudes of MoralResponsibility towards Nature, 3) Attitudes of Solidarity towards Nature, 4) Attitudes ofLove and Concern for Nature , 5) Attitude of not disturbing natural life. This researchwas carried out with the aim of observing and describing the existence of Ecocriticismin the Novel Panggil Aku Sakai by Ediruslan PE Amanriza.Key Words: Ecocriticism, Novel, Sakai